Study of one way product substitution on supply chain performance. (1st January 2011) - Routroy, Srikanta; Prashanth, T.; Ippili, Ravi Sankar
In today's competitive and dynamic business environment, companies are forced to find all the ways to enhance the product availability, increase the product variety and reduce inventory to achieve better performance in the supply chain. One may go for one way product substitution in the supply chain for increasing product availability and supply chain profit. A simulation model considering both, with product substitution and without product substitution, is developed in ARENA in order to study the impact of one way product substitution on supply chain performance. A numerical example is presented and sensitivity analysis is also carried out.